Sobre la diversitat de manifestacions literàries en la segona meitat del segle XV: contactes entres les obres i els autors - Garcia Sempere, Marinela (Caplletra. Revista Internacional de Filologia, 2003)
After highlighting the variety and extent of literary texts in the last decades of the 15th century and the importance of the literary tradition, the unsuitability of critical assumptions like the radical separation of profane and religious literature is pointed out. An example of this is given with the study of the «Istòria de la Passió» (Story of the Passion) by Fenollar/Martines, in which profane techniques are used and the March/Corella/Fenollar relationship is made clear. In the second part, the «Col·loqui de dames» (Ladies’ Dialogue) is read as an exaggerated counterpoint to the feminine chastity circulated in religious writings.